Internationalizing Communication Curriculum: An Assignment Examining Relational Communication Across Cultures. Issue 5 (3rd September 2018) - Suwinyattichaiporn, Tara; Johnson, Zac D.
Abstract: The base of relational communication curriculum is Eurocentric. Given the importance of global citizenship and cross-, as well as, inter- cultural communication competencies the following paper outlines the importance of internationalizing relational communication curriculum. Specifically, student pairs select a relational theory or concept and examine the current literature and knowledge base surrounding this topic. Then these pairs work to find an international peer, whom they will interview, in order to compare and contrast their experiences in relation to their topic. This assignment allows students to build multiple relationships, expand their worldview, and refine their own written and oral communication skills.